Once Upon a Time: Using Stories with Hard-to-Reach Audiences - M. F. Laurent; Linda E. Moody (Journal of Applied Communications, 1983)
When was the last time you listened to a good story? Remember the wonderful tales you heard while perched upon Grandmother's knee?